An Evaluation of Law Enforcement Capabilities in the Context of Chemical, Biological, Radiological and Nuclear Risk Perceptions: A Research In the Scope of Turkey and the United States of America - Oğur, EMRE; Cantürk, Nergis (The Bulletin of Legal Medicine, 2022)
Chemical, biological, radiological and nuclear (CBRN) incidents can occur as natural disaster, accident and intentional usage origins. While first two incident origins involve response in the context of disaster management, incidents that CBRN agents were used on purpose are evaluated in security concepts and involve jurisdical investigation. In recent years, at foremost international organizations call attention to increase the potential of intentional use of CBRN agents by radical terror groups. In this study, it is aimed to reveal the capabilities of law enforcement units and attitudes toward personnel training in the context of CBRN risk and threat for Turkey and the United States of America. In this research, qualitative research methodology and secondary data which was obtained from previous studies were utilized. At the end of the research, it is seen that the United States of America has reached a point with a 20-year professionalization process, however Turkey has passed “awareness” border and taking steps to develop a professional methodology.